Impact of community-based health insurance on child health outcomes: Evidence on stunting from rural Uganda - Emmanuel Nshakira-Rukundo; Essa Chanie Mussa; Nicolas Gerber; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2019)
While community-based health insurance (CBHI) becomes increasingly integrated into health systems in developing countries, there is still limited research and evidence on its probable health impacts beyond its functions for health financing or for facilitating access to services. Using a cross-sectional data from rural south-west Uganda, we apply a two-stage residual inclusion instrumental variables method to study the impact of community health insurance on stunting in children under five years. Results indicate that each year a household was enrolled in insurance was causally associated with a reduction in the probability of stunting of 5.7 percentage points. Predictive marginal effects show that children in households which have had insurance for at least 5 years had a probability of stunting of only 0.353 compared to 0.531 for children in households with no insurance. Households in CBHI were more likely to attend more free antenatal and postnatal care visits and report fewer illnesses and reported less health expenditures. Moreover, CBHI enrolment was also associated with reduced health costs. We recommend that developing countries should facilitate the expansion of community health insurance scheme not only for their contribution to health financing but even more for mortality and morbidity aversion.
Keywords: I13; I15; I10; I55; 330; Community-based health insurance; Child Stunting; Two-Stage Residual Inclusion; Rural Uganda